Sensitivity analysis of MHD hybrid nanofluid flow over a radially shrinking disk with heat generation - Khashi’ie, Najiyah Safwa; Mukhtar, Mohd Fariduddin; Zainal, Nurul Amira; Hamzah, Khairum; Waini, Iskandar; Mohd Kasim, Abdul Rahman; Pop, Ioan (Penerbit Akademia Baru, 2024)
This work features the numerical computation and statistical analysis (response surface and sensitivity) for the flow and thermal progress of an axisymmetric copper alumina/water hybrid nanofluid subjected to a permeable shrinking disk. The simultaneous factors of magnetic field (MHD), heat generation and suction parameter in the heat transfer development and flow characteristic are observed. The flow and energy equations are mathematically developed based on the boundary layer assumptions. These equations are then simplified with the aids of the similarity variables. The numerical results are then generated by the bvp4c solver in the Matlab software. The dual solutions are possible and exist up to a separation value upon the inclusion of suction effect. The increment of heat generation parameter from 0% to 1% reduces the heat transfer rate for all values of the stretching/shrinking parameter. For the response surface analysis, the responses (skin friction coefficient and heat transfer rate) are analyzed for three factors (magnetic, suction, heat generation) and three magnitudes (low, medium, high). Based on this analysis, the magnetic and suction parameters provide a significant effect on the skin friction with p-values < 0.05. Meanwhile, for the heat transfer coefficient, all factors give significant impact with zero p-values. Meanwhile, the sensitivity analysis reveals that the suction parameter has higher sensitivity to the heat transfer as compared to the magnetic and heat generation parameter. Even though these parameters being less sensitive, their influence on heat transfer remains statistically significant.